2017
DOI: 10.29252/ijrm.15.12.749
|View full text |Cite
|
Sign up to set email alerts
|

Ion channel gene expressions in infertile men: A case-control study

Abstract: Background: Infertility is described as not receiving pregnancy despite unprotected and regular sexual intercourse in a 1 yr period. It is detected by 15% of the couples. Male and female factor in the etiology may be detected in similar rates. Objective: The present study aims to investigate ion channel gene expression in semen samples of infertile male compared with fertile men. Materials and Methods: A total of 150 men who applied to the urology clinic due to infertility were divided into five equal groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…High expression levels of CATSPER3 mRNA have been observed in high-motile human spermatozoa, when compared to low-motile spermatozoa [ 31 ]. Further, CATSPER3 gene expression was observed to be decreased in spermatozoa from patients with AZ and oligoasthenoteratozoospermia (OAT), a condition that includes oligozoospermia (low number of sperm), AZ and teratozoospermia (abnormal sperm shape) [ 32 ]. For this gene, our results corroborate these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…High expression levels of CATSPER3 mRNA have been observed in high-motile human spermatozoa, when compared to low-motile spermatozoa [ 31 ]. Further, CATSPER3 gene expression was observed to be decreased in spermatozoa from patients with AZ and oligoasthenoteratozoospermia (OAT), a condition that includes oligozoospermia (low number of sperm), AZ and teratozoospermia (abnormal sperm shape) [ 32 ]. For this gene, our results corroborate these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that this gene is essential for sperm motility as well as the preparation of sperm for fertilization 80 . Similarly, the CATSPER4 gene (scaffold10: 17.41–17.42 Mb, survival group) is related with the male infertility 81 . The IGF2R gene was identified on scaffold5: 22.64–22.74 Mb in virus clearance group and it seems that the expression of this gene plays critical roles in pre-implantation of embryos 82 and birth weight 83 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in sperm cells, HVCN1 channels export H + more quickly and efficiently than other transporters or exchangers do [ 133 ]. In humans, HVCN1 monomers appear as a 32–35 kDa band in immunoblotting assays and are located in the principal piece of the sperm flagellum, close to CatSper [ 5 , 159 , 160 ]. In cattle, HVCN1 forms a band of around 32 kDa and distributes throughout the principal and terminal pieces of the sperm flagellum [ 22 ], whereas in pigs the molecular weight of each subunit is 35 kDa [ 3 , 137 ].…”
Section: Proton Transportersmentioning
confidence: 99%
“…The biochemical and biophysical changes associated with sperm capacitation have been extensively reported, and they include changes in ion concentration and internal pH (pH i ), plasma membrane properties, motion features, cell metabolism, and protein phosphorylation patterns [ 1 , 2 , 3 , 4 ]. It is widely accepted that ion flux is essential for sperm capacitation, and that small disturbances in the activity of ion channels may result in impaired fertility [ 1 , 5 , 6 , 7 , 8 ]. The most relevant ions inducing sperm capacitation are bicarbonate (HCO 3 − ) and calcium (Ca 2+ ), which act as second messengers triggering both sperm hypermotility and acrosomal reaction [ 1 , 9 ].…”
Section: Introductionmentioning
confidence: 99%